Performances evaluation of binary concrete designed with silica fume and metakaolin - Meddah, M.; Ismail, Mohamed; El-Gamal, S.; Fitriani, H. (Elsevier BV, 2018)
The use of various pozzolanic and cementitious materials not only has an environmental and economic impact, by the reduction of Portland cement clinker production, but also could significantly improve the strength and durability performances of concrete. Silica fume (SF) is a well-known and largely used pozzolanic material due to numerous improvements that could provide to concrete while metakaolin (MK) even with quite similar performance is still less popular in concrete industry. The present study investigates and compares the key mechanical properties and durability performances of binary concrete mixes designed with different replacement levels of SF and MK varying from 5% to 25% of Portland cement (PC). The results indicate that using both SF and MK in a partial substitution of PC could significantly improve strengths and durability performances of blended cement concrete mixes in comparison with the control PC-concrete. Meanwhile, SF-concrete seems to perform better than MK-concrete with regards to strength development and resistance to freezing-thawing while MK-concrete has exhibited a better performance with regard to carbonation and chloride ions ingress. Furthermore, although economical assessment showed an increase in the cost of concrete made with SF/MK due to the fact that SF/MK are more expensive than PC, environmental assessment revealed that significant reduction of the embodied CO 2 (ECO 2 ) is generated when using MK, and especially SF as a partial substitution of PC. Designing a binary SF and MK concretes may help towards producing clean and environmentally friendly concrete material.